2022
DOI: 10.3390/antiox11020323
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Effects of mitoTEMPO upon Lipopolysaccharide Challenge Are Due to Its Antioxidant Part, While Local Effects in the Lung Are Due to Triphenylphosphonium

Abstract: Mitochondria-targeted antioxidants (mtAOX) are a promising treatment strategy against reactive oxygen species-induced damage. Reports about harmful effects of mtAOX lead to the question of whether these could be caused by the carrier molecule triphenylphosphonium (TPP). The aim of this study was to investigate the biological effects of the mtAOX mitoTEMPO, and TPP in a rat model of systemic inflammatory response. The inflammatory response was induced by lipopolysaccharide (LPS) injection. We show that mitoTEMP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
(56 reference statements)
0
6
0
Order By: Relevance
“…Recent studies highlight the use of mitochondria-targeted antioxidants, such as Mi-toTEMPO, which typically utilize triphenylphosphonium for mitochondria targeting. The functional moiety of MitoTEMPO, acting as a trap for ROS, is delivered to mitochondria, where it can scavenge mitochondrial ROS and mitigate oxidative damage [26]. Furthermore, studies have shown that MitoTEMPO can modulate mitochondrial function and structure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies highlight the use of mitochondria-targeted antioxidants, such as Mi-toTEMPO, which typically utilize triphenylphosphonium for mitochondria targeting. The functional moiety of MitoTEMPO, acting as a trap for ROS, is delivered to mitochondria, where it can scavenge mitochondrial ROS and mitigate oxidative damage [26]. Furthermore, studies have shown that MitoTEMPO can modulate mitochondrial function and structure.…”
Section: Discussionmentioning
confidence: 99%
“…One such mitochondria-specific antioxidant is MitoTEMPO (2-(2,2,6,6tetramethylpiperidin-1-oxyl-4-ylamino)-2-oxoethyl) triphenylphosphonium chloride) [25]. In the case of MitoTEMPO, triphenylphosphonium is the mitochondrial-targeting moiety, which selectively accumulates in mitochondria due to its unusually high membrane potential, whereas the rest of the molecule is the functional moiety [26].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it has been shown that mitoTEMPO has a beneficial effect on the majority of organs due to its antioxidant part (TEMPO). Still, the beneficial impact on the lung is due to phosphonium, the positively charged transport part of mitoTEMPO [9]. This controversy in the action of antioxidants, which depends on different pathological settings, affected signaling pathways, and different body/cell compartments, is often called the pleiotropic effects of antioxidants.…”
Section: Pleiotropic Actions Of Ros and Antioxidantsmentioning
confidence: 99%
“…This combination makes a compound that works well to remove superoxide from the mitochondria. Mito-TEMPO is also expected to keep the quality of human spermatozoa that have been frozen and then thawed (27,28). Weidinger et al found that Mito TEMPO decreased the expression of nitric oxide synthase in the liver, as well as markers of liver and kidney damage (aspartate aminotransferase and alanine aminotransferase) (urea and creatinine) (27).…”
Section: The Effects Of Mito-tempo On Sperm Cryopreservationmentioning
confidence: 99%